Innovations Marketing System at Enterprises - Sabirova D. T. Diana Tagirovna; Kovalenko N. A. Natalya Aleksandrovna; Davletgareev N. R. Nail Rynadovich; Izvekova K. V. Karina (2017, 2017)
Title screen